Online employment platform selection by using fuzzy Analytic Hierarchy Process / Muhammad Iqbal Muhamidi and Mohd Halimi Ab Hamid - Muhamidi, Muhammad Iqbal; Ab Hamid, Mohd Halimi (College of Computing, Informatics and Media, UiTM Perlis, 2023)
E-recruitment is the application of technology to assist in the hiring process. In the modern world, erecruitment has changed how the organisation conducts their traditional recruitment procedure. These days, there are numerous networking sites that help companies find qualified candidates. For instance, MYFutureJob, LinkedIn, Indeed, and JobStreet have become important sources for finding qualified candidates for companies. These are the greatest employment portals in our country, assisting individuals in the recruitment process as there are more options to select the best applicant for each open position. So this study identifies the most preferred criteria and alternatives in choosing an online platform. To achieve these objectives, fuzzy AHP will be used to make a comparison between LinkedIn, MyFutureJob, Indeed, and Jobstreet which are often used by job-seekers to apply for jobs in Malaysia. A total of three jobseekers participated as maker decisions. Questionnaires were developed based on articles from journals and papers based on previous studies. Based on findings, LinkedIn is the superior employment platform website in Malaysia, surpassing MYFutureJob, JobStreet, and Indeed.